Muhammadiyah Dalam Mencerdaskan Kehidupan Bangsa Dengan Ilmu Pendidikan - Nur Hanifah, Aulia; Gunanding Setiani, Ririn; Hidayah, Astika Nurul (STAI Yogyakarta, 2024)
Muhammadiyah is an Islamic movement that preaches amar ma'ruf nahi munkar and tajdid based on the Qur'an and as Sunnah. Muhammadiyah is one that strongly upholds Islam, one of which is through the world of education. Education is an important factor which can shape human potential, personality, intelligence, noble character, self-control, religion and skills needed in self and society. To advance and educate the community, Muhammadiyah applies it by establishing several educational institutions that are modern, superior, and progressive. By still emphasizing the existence of Islamic values in accordance with Muhammadiyah's vision and mission. The purpose of the research is to find out how the strategy carried out by Muhammadiyah in increasing the existence of Islam in society both inside and outside through education. This research uses library research methods related to library data collection methods and data collection techniques in this research using document studies. The results showed that Muhammadiyah still upholds Islamic values through education. So that even though times have changed, Muhammadiyah still adheres to Islamic values by making modern-based reforms.